Size, Returns, and Value: Do Private Equity Firms Allocate Capital According to Manager Skill? - BRAUN, REINER; DORAU, NILS; JENKINSON, TIM; URBAN, DANIEL (Journal of Finance, 2026)
ABSTRACT Using a novel data set linking private equity (PE) deals to individual managers, we document evidence of manager skill in terms of generating net present value (NPV), a performance measure that captures both scale and returns. PE firms have strong economic incentives to raise larger funds and execute larger deals. While relative returns decline with scale, NPV persists and even increases. Skilled managers are entrusted with more capital and achieve better career outcomes, and approximately 40% of NPV is attributable to internal capital allocation decisions. These findings highlight the role of PE firms in creating value through performance‐based capital deployment.